2018
DOI: 10.1002/jcph.1107
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Safety of the β3‐Adrenoceptor Agonist Mirabegron and the Antimuscarinic Agent Solifenacin in the SYNERGY Trial

Abstract: There have been concerns that treatment of overactive bladder with β -adrenoceptor agonists may potentially have detrimental cardiovascular (CV) side effects. We evaluated the CV safety of mirabegron, a β -adrenoceptor agonist, alone and in combination therapy with the antimuscarinic agent solifenacin. The SYNERGY trial was a multinational, multicenter, randomized, double-blind, parallel-group, placebo and active-controlled phase 3 trial. Patients were randomized to receive solifenacin 5 mg + mirabegron 50 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, in support of the findings from PLUS, previous monotherapy studies with mirabegron and tamsulosin have not indicated that either of the therapies have significant effects on ECG parameters. 26,27 Furthermore, a recent large population-based study from Canada reported that mirabegron was not associated with a higher risk of cardiovascular events compared with other OAB treatments. 28 The investigators tracked hospitalizations and emergency visits for arrhythmias, tachycardia, myocardial infarction, and stroke over a 1-year period.…”
Section: Discussionmentioning
confidence: 99%
“…However, in support of the findings from PLUS, previous monotherapy studies with mirabegron and tamsulosin have not indicated that either of the therapies have significant effects on ECG parameters. 26,27 Furthermore, a recent large population-based study from Canada reported that mirabegron was not associated with a higher risk of cardiovascular events compared with other OAB treatments. 28 The investigators tracked hospitalizations and emergency visits for arrhythmias, tachycardia, myocardial infarction, and stroke over a 1-year period.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, cardiovascular side effects such as hypertension and prolonged QT interval on ECG are one of the main concerns under Mirabegron treatment (9). Extra caution should be taken in patients who have a history of hypertension and long QT syndrome (13).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…More recently, in 2021, Mirabegron is approved by the FDA for use in neurogenic detrusor overactivity (NDO) treatment in children (8). Mirabegron works by acting on the smooth muscles of the bladder, causing relaxation which results in the increase in bladder capacity without changing micturition pressure, voiding contraction, and post-void residual (7,9). Mirabegron can be used as monotherapy or in combination with anticholinergics (7,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…6 However, in an international, multicentre randomized double-blind parallel-group placebo-controlled trial of solifenacin and mirabegron, there were very few major cardiovascular events, including stroke, with no significant difference between control and treatment groups. 7 Pooled data from 13 studies has also found no evidence of increased stroke risk from mirabegron use compared to placebo after controlling for baseline cardiovascular characteristics. 8 However, mirabegron is now contraindicated in patients with severe uncontrolled hypertension and regular monitoring of blood pressure is recommended, particularly in patients with preexisting hypertension.…”
Section: Hypertensive Intracerebral Haemorrhagementioning
confidence: 99%